Cortical speech sound differentiation in the neonatal intensive care unit predicts cognitive and language development in the first 2 years of life. (25th June 2013) - Maitre, Nathalie L; Lambert, Warren E; Aschner, Judy L; Key, Alexandra P
Abstract : Aim: Neurodevelopmental delay in childhood is common in infants born preterm, but is difficult to predict before infants leave the neonatal intensive care unit (NICU). We hypothesized that event‐related potential (ERP) methodology characterizing the cortical differentiation of speech sounds in hospitalized infants would predict cognitive and language outcomes during early childhood. Methods: We conducted a prospective study of 57 infants in NICU (34 male, gestational age at birth 24–40wks), quantifying the amplitude of ERP responses to speech sounds before discharge (median gestational age 37.1wks), followed by standardized neurodevelopmental assessments at 12 months and 24 months. Analyses were performed using ordinary least squares linear regression. Results: Overall validity of constructs using all ERP variables, as well as sex, maternal education, gestational age, and age at ERP, was good and allowed significant prediction of cognitive and communication outcomes at 12 months and 24 months ( R 2 =22–42%; p <0.05). Quantitative models incorporating specific ERPs, gestational age, and age at ERP explained a large proportion of the variance in cognition and receptive language on the Bayley Scales of Infant Development at 24 months ( R 2 >50%; p <0.05). Interpretation: This study establishes ERP methodology as a valuable research tool to quantitatively assess cortical function in the NICU and to predict meaningful outcomes in early childhood. Abstract : This article is commented on by Ortiz‐Mantilla and Benasich on pages781–782 of this issue.